Insiden Infeksi Saluran Pernafasan Akut (ISPA) Pada Balita di Wilayah Kerja Puskesmas Pauh dan Faktor Determinannya: Acute Respiratory Infection (ARI) Incidence in Children Under Five Years at Pauh Public Health Center and Its Determining Factors - Ilmaskal, Radian; Wati, Linda; Hamdanesti, Rischa; Rahmi, Afzahul (JURNAL ILMU DAN TEKNOLOGI KESEHATAN TERPADU, 2023)
ARI cases dominate globally morbidity and mortality rates. ARI prevalence is increasing annually in the Padang city. This study aims to determine the determinants of the incidence of ARI in the Pauh Public Health Center. A quantitative study using a cross-sectional design was used. From October to December 2022, 141 mothers having children under five years took part in this study. Purposive sampling was used to collect the sample. Data was gathered using a structured questionnaire and analyzed univariately and bivariate using the chi-square test. The results showed that 64.5% of mothers were at risk, and more than half were at low educational and economic levels (71,6%) and (51,1%). There is a significant relationship between smoking habits (p=0.00; PR=1.53), immunization status (p=0.00; PR=1.80), and level of mother’s knowledge (p=0 .00; PR=1.68) with the incidence of ARI in children under five years. ARI in children under five years was significantly associated with smoking habits, immunization status and mother’s knowledges. It is hoped that family members, especially parents, will be more involved in their children's health and development, and that health workers can regularly educate the public about maternal and child health, especially ARI prevention, through various media and activate health cadres.